Accuracy of SeaHawk-HawkEye Ocean color CubeSat remote sensing reflectance products in globally distributed aquatic sites - Srinivas Kolluru; Sara Rivero-Calle; Philip J. Bresnahan; Susanne Kratzer; Timothy S. Moore; Thomas Schroeder; Sean Bailey; Alan Holmes; John M. Morrison; Gene F. Feldman; Liang Hong; Hiroto Higa; et al. (Remote Sensing of Environment, 2026)

The U.S. Ecosystem‐Based Fisheries Management Policy and Road Map: Assessing Progress and Applying Lessons Learned - Chris J. Harvey; Yvonne L. deReynier; Wendy E. Morrison; Jennifer L. Cudney; Dorothy M. Dick; Travis Ford; Karla Gore; Jamison M. Gove; Elliott L. Hazen; Jerome M. Hermsen; Keith Kamikawa; Mandy Karnauskas; et al. (Fish and Fisheries, 2025)
The need for ecosystem‐based fisheries management (EBFM) is growing more urgent as environmental changes, species shifts, new ocean uses, and other factors force oceans toward novel states. In the United States, the National Oceanic and Atmospheric Administration's National Marine Fisheries Service (NOAA Fisheries) developed an EBFM Policy in 2016, accompanied by a Road Map of 49 action items, to support marine ecosystem‐based management and conservation of fisheries, habitats, and protected species under U.S. federal jurisdiction. In 2024, NOAA Fisheries updated its EBFM Policy and Road Map and formed a team of science and policy experts to review progress and derive lessons learned during the first Road Map iteration. Four key lessons emerged: (1) progress toward EBFM in the U.S. has been substantial; (2) greater coordination could further enhance progress; (3) more effort is required to link science to management activities; and (4) human dimensions need greater integration throughout EBFM implementation. Enabling factors for progress on the Road Map included: champions at both the leadership and staff levels; use of participatory processes; motivation driven by ecosystem shocks and threats; and leveraging existing processes and frameworks. The updated EBFM Road Map supports historic and ongoing efforts to implement U.S. laws through improved coordination, integration, and knowledge exchange and can help to address many urgent challenges facing U.S. marine fisheries, habitats, and protected resources.

Environmental drivers of tropospheric bromine and mercury variability in coastal East Antarctica - Neil C. Page; Jenny A. Fisher; Stephen R. Wilson; Robyn Schofield; Robert G. Ryan; Sean Gribben; Andrew R. Klekociuk; Grant C. Edwards; Anthony Morrison (Atmospheric Environment, 2025)

Linking knowledge and action for climate-ready fisheries: Emerging best practices across the US - Julia G. Mason; Sarah J. Weisberg; Janelle L. Morano; Richard J. Bell; Mark Fitchett; Roger B. Griffis; Elliott L. Hazen; William D. Heyman; Kirstin Holsman; Kristin M. Kleisner; Katie Westfall; Michele K. Conrad; et al. (Marine Policy, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Drought at a coastal wetland affects refuelling and migration strategies of shorebirds - Alexandra M. Anderson; Christian Friis; Cheri L. Gratto-Trevor; Christopher M. Harris; Oliver P. Love; R. I. Guy Morrison; Sean W. J. Prosser; Erica Nol; Paul A. Smith (Oecologia, 2021)
Droughts can affect invertebrate communities in wetlands, which can have bottom-up effects on the condition and survival of top predators. Shorebirds, key predators at coastal wetlands, have experienced widespread population declines and could be negatively affected by droughts. We explored, in detail, the effects of drought on multiple aspects of shorebird stopover and migration ecology by contrasting a year with average wet/dry conditions (2016) with a year with moderate drought (2017) at a major subarctic stopover site on southbound migration. We also examined the effects of drought on shorebird body mass during stopover across 14 years (historical: 1974–1982 and present-day: 2014–2018). For the detailed comparison of two years, in the year with moderate drought we documented lower invertebrate abundance at some sites, higher prey family richness in shorebird faecal samples, lower shorebird refuelling rates, shorter stopover durations for juveniles, and, for most species, a higher probability of making a subsequent stopover in North America after departing the subarctic, compared to the year with average wet/dry conditions. In the 14-year dataset, shorebird body mass tended to be lower in drier years. We show that even short-term, moderate drought conditions can negatively affect shorebird refuelling performance at coastal wetlands, which may carry-over to affect subsequent stopover decisions. Given shorebird population declines and predicted changes in the severity and duration of droughts with climate change, researchers should prioritize a better understanding of how droughts affect shorebird refuelling performance and survival.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Evaluation of wireless sensor networks (WSNs) for remote wetland monitoring: design and initial results - Carl J. Watras; Michael Morrow; Ken Morrison; Sean Scannell; Steve Yaziciaglu; Jordan S. Read; Yu-Hen Hu; Paul C. Hanson; Tim Kratz (Environmental Monitoring and Assessment, 2014)

Brominated and fluorinated organic pollutants in the breast milk of first-time Irish mothers: is there a relationship to levels in food? - Iona Pratt; Wayne Anderson; Dominique Crowley; Sean Daly; Rhodri Evans; Alwyn Fernandes; Margaret Fitzgerald; Michael Geary; Declan Keane; John J. Morrison; Alan Reilly; Christina Tlustos (Food Additives & Contaminants: Part A, 2013)

Expression of Histone Deacetylases in Cellular Compartments of the Mouse Brain and the Effects of Ischemia - Selva Baltan; Amelia Bachleda; Richard S. Morrison; Sean P. Murphy (Translational Stroke Research, 2011)